FUNCTIONAL ACTIVITY OF PHAGOCYTES AND THE COMPLEMENT SYSTEM IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND CHRONIC PANCREATITIS - Zhelezniakova, N.M. (World of Medicine and Biology, 2012)
It is shown changes in the complement system, which are characterized by their reduced C3 and C5 components in patients with chronic obstructive pulmonary disease (COPD). Accession of chronic pancreatitis (CP) increases the data levels that can be regarded as an unfavorable factor. Also shows the changes in parameters of functional activity of neutrophilic granulocytes and activation of apoptosis. These circumstances are regarded as negative factors of disease progression and complications.У больных с сочетанным течением ХОЗЛ и хронического панкреатита определяются выраженные изменения в фагоцитарной активности нейтрофильных гранулоцитов с увеличением их апоптозной готовности. Данные изменения могут способствовать пролонгации фазы обострения заболевания и препятствовать развитию полноценной ремиссии, что, в свою очередь, приведет к развитию осложений.
Keywords: chronic obstructive pulmonary disease; chronic pancreatitis; pathogenesis; phagocytosis; the complement system